PERAN PEDAGANG WANITA DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI KELUARGA DI PASAR TRADISIONAL KECAMATAN RASAU JAYA - Novianto, Ocky; Nurjannah, Syamratun (Journal Of Islamic Ekonomic and Business, 2023)
ABSTRACT This study discusses the "role of women traders in the welfare of the family economy". Furthermore, the main focus is limited to sub-focuses, namely: what factors cause housewives to work as traders in the Rasau Jaya traditional market, what kinds of goods are traded by women traders in the Rasau Jaya traditional market, how are women's income fluctuations? who trade in the Rasau Jaya traditional market, is the income of the women traders in the Rasau Jaya traditional market able to improve the economic welfare of their families. This type of research uses a qualitative descriptive method, which means descriptive research is to investigate circumstances, conditions or others. The primary data obtained in this study were from women who became traders in the traditional Rasau Jaya market and the market manager, then secondary data was obtained from books, journals, articles related to the research. The results of this study are: Most of the reasons for choosing a profession as a trader are economic motives and a small part are not, Merchandise traded by all female traders is halal and good for consumption, During the covid-19 pandemic there was only 1 respondent who did not experience a decrease in income respondents while other traders experienced a decline. Keywords: Role of female traders, family welfare